Climate change in Europe: How to adapt our higher education curricula and involve the students and the teachers - Van Loon, Karin; Kalambura, Sanja; Paixão, Susana; Ploomipuu, Inga (Crisis Management Days, 2024)
Climate change has become the most pressing problem today. This will have an impact on human health. Therefore, health and environmental policies must aim to prevent their negative effects, and policy makers, educational institutions, have a crucial role to play in this regard World Health Organization (2021). To respond to a need to incorporate environmental and sustainability issues in the higher education curricula, four European higher education institutions decided to joint their competences to build five ECTS international, collaborative, and multidisciplinary online course modules focused on environment, sustainability, and health. A French study concludes that incorporating environmental and sustainability issues into the initial and higher training become a need in the education systems. There is also a need to train the teachers (Bortzmeyer, 2021). The final report of the association “Shifters Belgium” gives the conclusion of an analysis of curricula in Higher Education and a survey of the expectations of the students to achieve Carbon neutrality in 2050 regarding the European Green Deal. This survey shows that 80% of the students are worried about climate change. 87% of them think that Universities and University Colleges must organize modules on climate change (The Shifters, 2022). The four partner institutions received an Erasmus+ subvention, for 3 years to develop this online course. The higher education institutions are Brussels-Brabant University College (Belgium), University of Applied Sciences Velika Gorica (Croatia), Polytechnic of Coimbra (Portugal) and Tartu Health Care College – Tartu (Estonia). The aim of the course is to enhance the students’ interest and develop the scientific, technological, and socio-political foundations in the field of environment, sustainability, health as well as communication, English and crisis management skills. The process involves the teachers and students in a co-construction way and, through a situated learning environment (Slock, C., Netanyahu, S. (2021). To construct together this courses-module, each year, the partners develop a part of the module in a collaborative way with teachers and students of the four partner institutions. As the courses are different, the contributions of each institution and each teaching team are complementary. The partners bring specialist skills in science, technology, safety and crisis management, health, as well as language and communication. It will take 3 years to create, improve and validate the module. Concretely, the collaborative moments occur twice a year in the form of online courses in November and mobility activities in February. Three different topics will be developed: year 1: energy crisis in the partner countries, year 2: analysis methods in the field of environment, year 3: green smart factories. To improve interculturality, activities are spent each year in another country. The first year, the face-to-face activities took place in Estonia. The second year will take place in Portugal and the third year in Belgium. 40 students and 12 teachers took part in the face-to-face activities. The aim of this paper is to present the methodology and the partial results after one year, based on quantitative and qualitative indicators.